A number theory problem by Wildan Bagus Wicaksono

a = 3 + 4 3 + 4 3 + 4 b = a 2 c = b 2 \large \begin{aligned} a & = 3+\frac {4}{3+\frac {4}{3+\frac {4}{\ddots}}} \\ b & = \frac { a }{ 2 } \\ c & = \frac { b }{ 2 } \end{aligned}

For a a , b b and c c as defined above and k = 0 2 a 3 b 7 c 3 k ( 2 a 3 b 7 c k ) = ( 2 ) m \displaystyle \sum _{ k=0 }^{ { 2 }^{ a }{ 3 }^{ b }7^{ c } }{ { 3 }^{ k } { { 2 }^{ a }{ 3 }^{ b }7^{ c } \choose k }} = \left(\sqrt 2\right)^m , find m m .


The answer is 4032.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 18, 2017

a = 3 + 4 3 + 4 3 + 4 a = 3 + 4 a a 2 3 a 4 = 0 ( a 4 ) ( a + 1 ) = 0 a = 4 Note that a > 0 b = a 2 = 2 c = b 2 = 1 \begin{aligned} \large a & = \large 3 + \frac 4{3+\frac 4{3+\frac 4{\ddots}}} \\ \implies a & = 3+\frac 4a \\ a^2 -3a - 4 & = 0 \\ (a-4)(a+1) & = 0 \\ \implies a & = 4 & \small \color{#3D99F6} \text{Note that }a > 0 \\ \implies b & = \frac a2 = 2 \\ \implies c & = \frac b2 = 1 \end{aligned}

Therefore,

S = k = 0 2 a 3 b 7 c 3 k ( 2 a 3 b 7 c k ) = k = 0 2 4 3 2 7 1 3 k ( 2 4 3 2 7 1 k ) = k = 0 1008 3 k ( 1008 k ) Note that ( 1 + x ) n = k = 0 n ( n k ) = ( 1 + 3 ) 1008 = 4 1008 = ( 2 ) 4 × 1008 = ( 2 ) 4032 \begin{aligned} S & = \sum_{k=0}^{2^a3^b7^c} 3^k {2^a3^b7^c \choose k} = \sum_{k=0}^{2^43^27^1} 3^k {2^43^27^1 \choose k} = \sum_{k=0}^{1008} 3^k {1008 \choose k} & \small \color{#3D99F6} \text{Note that }(1+x)^n = \sum_{k=0}^n {n \choose k} \\ & = (1+3)^{1008} = 4^{1008} = \left(\sqrt 2 \right)^{4 \times 1008} = \left(\sqrt 2 \right)^{4032} \end{aligned}

m = 4032 \implies m = \boxed{4032}

a = 3 + 4 3 + 4 3 + 4 a = 3 + 4 a a 2 = 3 a + 4 0 = a 2 3 a 4 0 = ( a 4 ) ( a + 1 ) a = 4 , a = 1 \large a=3+\frac { 4 }{ 3+\frac { 4 }{ 3+\frac { 4 }{ \ddots } } } \\ \large a=3+\frac { 4 }{ a } \\ { a }^{ 2 }=3a+4\\ \large 0={ a }^{ 2 }-3a-4\\ 0=(a-4)(a+1)\\ \large \Rightarrow a=4,a=-1

Because 3 + 4 3 + 4 3 + 4 > 0 \large 3+\frac { 4 }{ 3+\frac { 4 }{ 3+\frac { 4 }{ \ddots } } } >0\\ , so the value of 3 + 4 3 + 4 3 + 4 = 4 \large 3+\frac { 4 }{ 3+\frac { 4 }{ 3+\frac { 4 }{ \ddots } } } =4\\ .

b = a 2 b = 4 2 b = 2 c = b 2 c = 2 2 c = 1 b=\frac { a }{ 2 } \\ b=\frac { 4 }{ 2 } \\ b=2\\ c=\frac { b }{ 2 } \\ c=\frac { 2 }{ 2 } \\ c=1

= k = 0 2 a 3 b 7 c 3 k ( 2 a 3 b 7 c k ) = k = 0 2 4 3 2 7 1 3 k ( 2 4 3 2 7 1 k ) = k = 0 16 9 7 3 k ( 16 9 7 k ) = k = 0 1008 3 k ( 1008 k ) = 3 0 ( 1008 0 ) + 3 1 ( 1008 1 ) + 3 2 ( 1008 2 ) + . . . + 3 1007 ( 1008 1 ) + 3 1008 ( 1008 1008 ) \large =\sum _{ k=0 }^{ { 2 }^{ a }{ 3 }^{ b }{ 7 }^{ c } }{ { 3 }^{ k }\left( \begin{matrix} { 2 }^{ a }{ 3 }^{ b }{ 7 }^{ c } \\ \large k \end{matrix} \right) } \\ \large =\sum _{ k=0 }^{ { 2 }^{ 4 }{ 3 }^{ 2 }{ 7 }^{ 1 } }{ { 3 }^{ k }\left( \begin{matrix} 2^{ 4 }{ 3 }^{ 2 }{ 7 }^{ 1 } \\ \large k \end{matrix} \right) } \\ \large =\sum _{ k=0 }^{ 16\cdot 9\cdot 7 }{ { 3 }^{ k }\left( \begin{matrix} 16\cdot 9\cdot 7 \\ \large k \end{matrix} \right) } \\ \large =\sum _{ k=0 }^{ 1008 }{ { 3 }^{ k }\left( \begin{matrix} 1008 \\ k \end{matrix} \right) } \\ \large ={ 3 }^{ 0 }\left( \begin{matrix} 1008 \\ \large 0 \end{matrix} \right) +{ 3 }^{ 1 }\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) +{ 3 }^{ 2 }\left( \begin{matrix} 1008 \\ 2 \end{matrix} \right) +...+{ 3 }^{ 1007 }\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) +{ 3 }^{ 1008 }\left( \begin{matrix} 1008 \\ \large 1008 \end{matrix} \right)

Based on ( a + b ) n = ( n 0 ) a 0 b n + ( n 1 ) a 1 b n 1 + ( n 2 ) a 2 b n 2 + . . . + ( n n 1 ) a n 1 b 1 + ( n n ) a n b 0 { \left( a+b \right) }^{ n }=\left( \begin{matrix} n \\ 0 \end{matrix} \right) { a }^{ 0 }{ b }^{ n }+\left( \begin{matrix} n \\ 1 \end{matrix} \right) { a }^{ 1 }{ b }^{ n-1 }+\left( \begin{matrix} n \\ 2 \end{matrix} \right) { a }^{ 2 }{ b }^{ n-2 }+...+\left( \begin{matrix} n \\ n-1 \end{matrix} \right) { { a } }^{ n-1 }{ b }^{ 1 }+\left( \begin{matrix} n \\ n \end{matrix} \right) { a }^{ n }{ b }^{ 0 }

So we get

= 3 0 ( 1008 0 ) + 3 1 ( 1008 1 ) + 3 2 ( 1008 2 ) + . . . + 3 1007 ( 1008 1 ) + 3 1008 ( 1008 1008 ) = ( 1008 0 ) 1 1008 3 0 + ( 1008 1 ) 1 1007 3 1 + ( 1008 2 ) 1 1006 3 2 + . . . + ( 1008 1 ) 1 1 3 1007 + ( 1008 1 ) 1 0 3 1008 = ( 1 + 3 ) 1008 = 4 1008 = 2 2016 \large ={ 3 }^{ 0 }\left( \begin{matrix} 1008 \\ \large 0 \end{matrix} \right) +{ 3 }^{ 1 }\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) +{ 3 }^{ 2 }\left( \begin{matrix} 1008 \\ 2 \end{matrix} \right) +...+{ 3 }^{ 1007 }\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) +{ 3 }^{ 1008 }\left( \begin{matrix} 1008 \\ 1008 \end{matrix} \right) \\ \large =\left( \begin{matrix} 1008 \\ \large 0 \end{matrix} \right) { 1 }^{ 1008 }{ 3 }^{ 0 }+\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) { 1 }^{ 1007 }{ 3 }^{ 1 }+\left( \begin{matrix} 1008 \\ \large 2 \end{matrix} \right) { 1 }^{ 1006 }{ 3 }^{ 2 }+...+\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) { 1 }^{ 1 }{ 3 }^{ 1007 }+\left( \begin{matrix} 1008 \\ \large 1 \end{matrix} \right) { 1 }^{ 0 }{ 3 }^{ 1008 }\\ \large ={ (1+3) }^{ 1008 }\\ ={ 4 }^{ 1008 }\\ \large ={ 2 }^{ 2016 }

2 2016 = 2 m 2 2016 = 2 1 2 m 2016 = 1 2 m m = 4032 \large { 2 }^{ 2016 }={ \sqrt { 2 } }^{ m }\\ \large { 2 }^{ 2016 }={ 2 }^{ \frac { 1 }{ 2 } m }\\ \large \Rightarrow 2016=\frac { 1 }{ 2 } m\\ \large \therefore m=4032

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...